Analysis of Teaching Methods That Outstanding Professors Use in Social Science - Castañeda-Meneses, Marta (2019)
The study aims to analyze teaching methods used by primary school teachers recognized as outstanding by the Chilean Ministry of Education from the perspective provided by key social concepts. From a qualitative point of view, the study uses a focus group as an initial information gathering technique and, mainly, focuses on non-participating observation of history, geography, and social science classes. The group is made up of teachers from the school system who are recognized as outstanding. The data are analyzed from the perspective of key social concepts, in this case: time, space, coexistence, identity and change, and from the teaching methods used. The main conclusion of the study is that the teaching models show a traditional perspective, mainly associated with an expository method, a methodological option that does not rule out the student body, which, from a participatory role, cedes the protagonism to the teaching staff in their role as a guide to learning.